« L’île de Beauté » qui est maudite Le pervers rêve corse de Prosper Mérimée - Sokołowicz, Małgorzata (Romanica Silesiana)
The article describes the vision of Corsica emerging from the works of Prosper Mérimée. Known for its picturesque landscapes and the vendetta practiced by its inhabitants, the island became a popular literary motif already in the second half of 18th century. However, Mérimée copes with this “Corsican myth” in a very original way. By deriding the boredom of many young Europeans of his times, he makes them fascinated with the savage island, to really terrify them, afterwards, with its terrible cruelty. Moreover, those who want to forget this traumatic Corsican experience do not manage to do it as the perverse dream has made them addicted to its cursed beauty. Key words: Mérimée, Corse, boredom, Colomba, beauty, curse, dream